15 COLLAPSIN RESPONSIVE MEDIATOR PROTEIN-5 AUTOANTIBODY-ASSOCIATED PARANEOPLASTIC NEUROLOGIC DISORDER IN A PATIENT WITH GASTRIC ADENOCARCINOMA. (1st January 2006) - Arledge, S.; Hamilton, D.; Elkins, S.
Abstract : Introduction: We report a case of CRMP-5 autoantibody-associated paraneoplastic neurologic disorder in a patient with gastric adenocarcinoma. Case Report: A 59-year-old man with hypertension and coronary artery disease was diagnosed with stage IIIA gastric adenocarcinoma. He underwent total gastrectomy and subsequently received adjuvant concomitant radiation therapy and chemotherapy consisting of 5-FU and leucovorin. Approximately 2 months after diagnosis he began having choreiform movements of all extremities along with depression and diffuse abdominal pain. CT scan of the brain showed no abnormalities. A paraneoplastic antibody panel revealed the presence of CRMP-5 IgG in his serum by Western blot. CT scan of the chest, abdomen, and pelvis, as well as PET scan, were performed to look for evidence of recurrence of his gastric cancer or an occult second malignancy. These tests were negative for the presence of any disease. Discussion: Paraneoplastic neurologic disorders are often found weeks to months prior to the diagnosis of a malignancy. CRMP-5 autoantibody has been associated with neurologic disorders in small cell lung cancer and thymoma most often, with few case reports of association with renal cell carcinoma and lymphoma. This is the first known reported case of CRMP-5 autoantibody-associated paraneoplastic neurologic disorder in a patient with gastric adenocarcinoma. The most effective treatment of this disorder is treatment of the underlying malignancy; however, this patient has already completed his treatment and has no evidence of disease. We will follow closely for disease recurrence or presentation of a second primary malignancy.